ЭТНОПЕДАГОГИЧЕСКАЯ КОМПЕТЕНЦИЯ КАК ВАЖНАЯ СОСТАВЛЯЮЩАЯ ЭТНОКУЛЬТУРОЛОГИЧЕСКОЙ КОМПЕТЕНТНОСТИ БУДУЩИХ УЧИТЕЛЕЙ - Курбаниязов, М. (SCIENCE and SOCIETY, 2022)
This article discusses the definition of a number of principles for the formation of the teacher’s ethnopedagogical competence, as well as proposals for their grouping.